The Transformation of a Cultural Ideal in the Theories of Education According to Plato’s Line - Bazaluk, Oleg (Studia Warmińskie, 2019)
In the paper, we considered the cultural ideal as the basic feature that distinguishes the theories of education according to Plato’s line from the theories of education according to Isocrates’ line. By example from the history of culture, we have shown the significance of cultural ideals in the theories of education of Antiquity, the Middle Ages and the Modern Age. In paper, authors tried to solve two objectives: firstly, to consider the consistency of the cultural ideal of an “intelligent person” with modern knowledge of the experience of being of Dasein-the-One; secondly, to propose a new cultural ideal, as a lighting, as a way to build an ideal Earth’s Republic. The authors stand on the point of view, that at the beginning of the 21st century, the Earth’s civilization for the first time manifested as a planetary force and this tendency should be correspondingly reflected at the philosophy of contemporary education. The authors considered the criticism of the Modern Age ideal of an “intelligent person” and proposed a new cultural ideal, which we called the metaphor “Those Who Transform the Universe.” Mentioned ideal is lighted the chasm that is between the authenticity and inauthenticity existence, between the Selbst and the das Man.